Rail‐suicide prevention: Systematic literature review of evidence‐based activities. (14th July 2016) - Barker, Emma; Kolves, Kairi; De Leo, Diego
Abstract: Background: Rail‐related suicide is a relatively rare but extremely lethal method of suicide that can have far‐reaching consequences. Objective: The aim of the systematic literature review was to analyze the existing literature on the effectiveness of rail‐suicide prevention activities. Data sources: Databases used were Scopus, Medline, and ProQuest. Search terms: The search terms used were "suicid*, " "prevent*, " "rail*, " or "train." Eligibility criteria: English‐language studies published in peer‐reviewed journals between 1 January 1990 and 30 April 2015 that presented an overview of rail‐related suicide prevention activities and included an analysis of effectiveness were used. Results: We retrieved 1, 229 results in the original search with nine papers presenting empirical evidence. Three studies in the review analyzed the effectiveness of platform screen doors and another three analyzed the installation of blue lights, two papers analyzed the effectiveness of suicide pits, and one included the influence of media reporting guidelines. Conclusion: Platform screen doors, suicide pits, blue lights, and improved media guidelines all have the potential to reduce rail‐related suicide events and deaths. Limitations: The review was restricted to English‐language peer‐reviewed papers published within the chosen time period.